Parusnyj sport (Analiticheskaya spravka vystupleniya sbornoj komandy Rossii po parusnomu sportu v sezone 2001 g.) - Slautina, I. N. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
At first the actual situation in sailing is analysed. Then the performances of the Russians at the main competitions in the last years are listed as well as the coasts for different measures in the prepration for these events.